-6x+24=-4x+4

Simple and best practice solution for -6x+24=-4x+4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6x+24=-4x+4 equation:


Simplifying
-6x + 24 = -4x + 4

Reorder the terms:
24 + -6x = -4x + 4

Reorder the terms:
24 + -6x = 4 + -4x

Solving
24 + -6x = 4 + -4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '4x' to each side of the equation.
24 + -6x + 4x = 4 + -4x + 4x

Combine like terms: -6x + 4x = -2x
24 + -2x = 4 + -4x + 4x

Combine like terms: -4x + 4x = 0
24 + -2x = 4 + 0
24 + -2x = 4

Add '-24' to each side of the equation.
24 + -24 + -2x = 4 + -24

Combine like terms: 24 + -24 = 0
0 + -2x = 4 + -24
-2x = 4 + -24

Combine like terms: 4 + -24 = -20
-2x = -20

Divide each side by '-2'.
x = 10

Simplifying
x = 10

See similar equations:

| 2(1/3x-12)^2+(5/3x-12)+2=0 | | x^2-21=-21 | | 2(b+2)-(6+b)=-6 | | 83.3x=30 | | 3(3x-4)=24 | | 3/6*8/4*2/3*6/3 | | X^2-5x-120=180 | | (6x^2+36x+28)/(x+5) | | 0.07q+0.7=0.17q-9.5 | | 9-6+u=(27-24)(2)+u | | -13+5h=12 | | 2x+14=5x+5 | | 56-(2x+13)=2(x+9)+x | | 5n+6=-7(5n-6)-6n | | (1/2x-1)^2+(1/2x-1)-72=0 | | 4x+7-6=54x+4 | | 2c^3+2c^2-4c=0 | | 9x^4+15x^3-36x^2-60x=0 | | 7.6p-3.1=42.5 | | 5.2=.04m | | 3(3x-12)=24 | | 13+1x=1 | | 2x+4-5x(x-5)=5x | | 2-6n=-5(4-n) | | -4(-8+2)=-4x-8 | | 2x^4-56x^2+150=0 | | 13x+12= | | -4c-18=-6c-8 | | 2x+10-6x=19-18x+14x-9 | | (3/5)x=15 | | -5/2=0.04m | | 5x+10=-2x+3 |

Equations solver categories